Rooftop gardening: Avenue for healthy living - Bisht, Kamini; Bisht, Kavita; Sharma, Anamika; Singh, Y P (Indian Horticulture, 2022)
Rooftops are underutilized and rarely-considered urban spaces with great potential for terrace gardening. Rapid urbanization, industrialization, land ceiling, construction of buildings, wide roads, offices, markets have resulted in non-availability of land for kitchen gardening activities in big cities and towns. Metropolitan cities have driven out agriculture from their boundaries. Owing to changing climatic conditions, a lot of pesticides and chemicals used in cultivation of fruits and vegetables affect the health of human beings.